HEALTH EDUCATION “MOLETAS” IMPROVING KNOWLEDGE AND AT TOWARD OBESITY PREVENTION AMONG ADOLESCENTS - Egy Sunanda Putra; Ary Irfan; Gisella Martiani (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Obesity is an emerging health problem among adolescents and can have long-term health consequences. One innovative approach to improving knowledge and attitudes toward obesity prevention is through the use of educational games. The MOLETAS (Monopoly Obesity) educational media was developed to deliver health messages in an engaging and interactive way. This study aimed to determine the effect of health education using the MOLETAS media on improving knowledge and attitudes toward obesity prevention among adolescents. This research employed a quantitative pre-experimental design with a one-group pretest–posttest approach. A total of 70 students were selected using random sampling in Senior High School 10, Jambi City. Data were collected using validated questionnaires on knowledge and attitudes. The data were analyzed using the Wilcoxon test, as the distribution was non-normal according to the Kolmogorov–Smirnov test. The results showed a significant increase in the mean knowledge score (P < 0.001; MD = 1.7) and mean attitude score (P < 0.001; MD = 14.09) after the intervention. These findings indicate that the MOLETAS educational media effectively improves students’ knowledge and attitudes toward obesity prevention.